Triatoma rubrovaria (Blanchard, 1843) (Hemiptera: Reduviidae) I: isoenzymatic and chromatic patterns of five populations from the State of Rio Grande do Sul, Brazil - Carlos Eduardo Almeida; Raquel S Pacheco; François Noireau; Jane Costa (Memorias do Instituto Oswaldo Cruz, 2002)
Triatoma rubrovaria has become the most frequently captured triatomine species since the control of T. infestans in the State of Rio Grande do Sul (RS), Brazil. In order to evaluate the genetic variability of this species, field collections were performed in four municipalities where it has been reported and distant from 75 to 322 km. Specimens were analyzed by color pattern and isoenzymes. Nine enzymatic loci were interpreted from nine enzymatic systems. The Santiago population was isolated from the others with chromatic monomorphism and diagnostic alleles at Idh and Pgm loci. The study shows the existence of, at least, two distinct populations of T. rubrovaria in RS with different phenotypic and genetic pattern.